Teachers’ Perspective Toward Self-Reflection to Improve Teaching Performance - Bintang Hemas Widyanita; Sukma Nur Ardini; Salimatin Mufidah (English Language Education Department, Universitas Majalengka, 2023)
The purpose of this research is to describe the teachers' opinion about self-reflection which improves their teaching performance. This research was done at SMA Islam Sultan Agung 1 Semarang with a total number of population was four English teachers. An open-ended questionnaire was used to collect data in this research. The questionnaire was distributed to respondents through google form on May 2023. After the data were collected, they were analyzed thematically. The data were extracted and discussed into the following six themes, namely (a) important form of evaluation, (b) perfect timing, (c) personal or collaborative self-Reflection, (d) documentation, (e) the benefit, (f) challenging, (g) boredom, and (h)teaching performances. Based on the results and discussion from the previous section, it can be concluded that teachers acquire self-awareness, identify areas for improvement, adjust their methods, respond to student needs, and strive for continual professional progress through self-flection.